+0  
 
+1
59
1
avatar

solve y(1+x2)y'-x(1+y2)=0 and find a particular solution that satisfies the initial condition y(0)=√3

Guest Aug 4, 2017
Sort: 

1+0 Answers

 #1
avatar+75333 
+1

 

y(1+x^2)y'-x(1+y^2) = 0     this is a separable equation

 

y ( 1 + x^2)y'  =  x ( 1 + y^2)   rearrange as

 

[ y] / [ 1 + y^2 ] y'  =  [x] / [ 1 + x^2]   integrate both sides

 

∫ y / [ 1 + y^2] dy  = ∫ x / [ 1 + x^2]  dx

 

(1/2) ln ( 1 + y^2)  =   (1/2) ln ( 1 + x^2) + C

 

ln (1 + y^2)  =  ln ( 1 + x^2 ) + C    exponentiate both sides

 

e^[ln (1 + y^2) ] =  e ^ [  ln ( 1 + x^2 ) + C]

 

1 + y^2  =  e^[ ln ( 1 + x^2)] * e^C       →     let e^C   =  C2

 

1 + y^2  =  (1 + x^2) * C2

 

y^2  = ( 1 + x^2) *C2  - 1

 

y = ± √  [   ( 1 + x^2) *C2  - 1 ]

 

y (x) =   ± √  [   C2x^2 + C - 1 ]

 

Now....since the intial condition is that   y(0)  = √3  .....the positive root must be correct....solving for C2, we have that

 

√3  =   √  [   C2(0)^2 + C2  - 1 ]

 

√3 = √ [ C2 - 1]

 

3  = C2 - 1

 

C2 = 4

 

So....the particular solution is   y(x)  = √  [   4x^2 + 4  - 1 ]  =   √  [  4x^2 + 3 ]

 

 

 

cool cool cool

CPhill  Aug 4, 2017

7 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details